The Role Of Mental Health Training In Improving Nurses' Ability To Care For Patients With Mental Disorders - Ariyanti, Sri; Mora, Mora; Sipahutar, Pongky; Ningsih, Warti; Hadi, Irwan; Pannyiwi, Rahmat (Jurnal EduHealth, 2024)
Mental health training plays a crucial role in improving nurses' ability to care for patients with mental disorders, but challenges in conventional training still exist. This study aimed to evaluate the effectiveness of technology-based mental health training, specifically e-learning and VR/AR simulation, in improving nurses' knowledge, skills and confidence. The research method involved an experimental design with a randomized control group and monitoring of nurses' performance before and after the training. The results showed significant improvements in nurses' knowledge, practical skills, and confidence after undergoing technology-based training. The implication is that the use of technology in mental health training can improve the quality of care for patients with mental disorders and strengthen nurses' clinical practice.